1999
DOI: 10.1093/hmg/8.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Association of ulcerative colitis with rare VNTR alleles of the human intestinal mucin gene, MUC3

Abstract: Ulcerative colitis (UC), a common form of inflammatory bowel disease, is a multifactorial disorder with significant genetic influence. Recently, evidence of linkage on chromosome 7q near the intestinal mucin gene MUC3 was reported by an affected sib-pair analysis. Previous reports indicate a possible mucin abnormality in UC patients, but whether genetic differences in a specific mucin gene are associated with UC is unknown. Here we analysed polymorphisms of variable number of tandem repeats (VNTRs) within this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 33 publications
1
57
0
2
Order By: Relevance
“…We could not explain the dominant effect observed in the association study we reported recently (Kyo et al 1999), because human MUC3 was considered to be a secretory mucin and mucin protein encoded by a common allele would compensate for the function of that encoded by a rare allele. Furthermore, it has been unknown whether the 51-bp repetitive regions lie in a single gene, making an internal duplication, or whether they lie in two tandemly arrayed genes (Gum et al 1997).…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…We could not explain the dominant effect observed in the association study we reported recently (Kyo et al 1999), because human MUC3 was considered to be a secretory mucin and mucin protein encoded by a common allele would compensate for the function of that encoded by a rare allele. Furthermore, it has been unknown whether the 51-bp repetitive regions lie in a single gene, making an internal duplication, or whether they lie in two tandemly arrayed genes (Gum et al 1997).…”
Section: Introductionmentioning
confidence: 74%
“…Five micrograms of genomic DNA were digested to completion with restriction enzyme Pvull (Toyobo, Tokyo, Japan), run in 0.5% agarose gel (13 cm long) at 25 V for 48 h and transferred to a nylon membrane, as described previously (Kyo et al 1999). Blots were proved with a clone composed of a 51-bp repeat (51R), a 498-bp clone corresponding to a part of 1125-bp repeat unit located between Pvull-restriction site and 51-bp repeat (1125D), a 796-bp clone corresponding to a semi-unique region located between the 177-bp repeat and the 51-bp repeat (SUR), or three distinct parts of the 3Ј region of "MUC3", the sequence of which Gum et al (1997) reported previously (3TR-1, 3TR-2, or 3TR-3; Fig.…”
Section: Southern Blot Analysismentioning
confidence: 99%
See 3 more Smart Citations